Unraveling the mechanism of mulberry leaf in alleviating hyperuricemia: key role of kaempferol by modulating AKT pathway and gut-kidney axis - Huang, Jiawei; Wang, Qianqian; Guo, Xiaowen; Niu, Yuanyuan; Huang, Junhong; Zhang, Boyi; Guo, Zixuan; Wang, Zilong; Feng, Shuying (Frontiers in Microbiology, 2026)
BackgroundMulberry leaf (Morus alba L.) is an edible plant that has been found to have medicinal effects in the treatment of hyperuricemia (HUA). The bioactive compounds of mulberry leaf and their mechanisms of action have not been determined yet.MethodsIn-silico methodologies were used to identify bioactive compounds and to determine the underlying mechanisms of mulberry leaf. In order to verify the biochemical mechanism and intestinal microbiota, in vivo experiments were conducted.ResultsKaempferol was identified as the principal bioactive compound, while the key targets were AKT1 and TNF. Molecular docking and dynamics simulations revealed that AKT1-kaempferol and TNF-kaempferol complexes showed strong and stable binding pattern after a 100 ns simulation. In vivo studies demonstrated that kaempferol exerted significant anti-HUA effects. Specifically, kaempferol reduces AKT expression and phosphorylation, which may in turn reduces the oxidative stress and inflammatory pathways and signal transmission of the kidneys. Meanwhile, the application of kaempferol attenuated gut microbiota dysbiosis caused by HUA.ConclusionKaempferol may regulate UA metabolism and inflammatory injury by modulating the AKT signaling pathway, and exert its effects on the gut-kidney axis and restoring gut microbiota composition.